Gambaran Klinis dan Histopatologi Keratosis Seboroik : Clinical and Histopathological Features of Seborrheic Keratosis - Mayati Suwoko, Wika Umayatul Choiroh; Yuniaswan, Anggun; Retnani, Diah (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Seborrheic keratosis is the most common benign epidermal tumor and is often found in the elderly, which is about 20% of the total population. The exact cause of this disorder is still not clearly known. Sun exposure is said to be one of the causes of seborrheic keratosis. Lesions can be flat, circumscript and dull-looking brown spots, with a smooth, velvety surface, can also take the form of hyperpimented papules or plaques, round or oval, circumscript, such as coated wax (waxy) with a verrucosa surface, or a picture of sticking